2018
DOI: 10.1097/rlu.0000000000002167
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Corpus Metastasis From Rectal Adenocarcinoma Detected Using 18F-FDG PET/CT

Abstract: We report an unusual case of uterine corpus metastasis from rectal adenocarcinoma detected using F-FDG PET/CT. A 47-year-old woman was diagnosed with rectal adenocarcinoma and treated with surgery and radiochemotherapy 3 years ago. During follow-up, she presented with lower abdomen pain and elevated tumor markers, but ultrasonography findings were unremarkable. We performed an F-FDG PET/CT scan, which showed intense F-FDG avidity in the myometrium of the uterine corpus. Uterine corpus metastasis was suspected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It highlights the unique advantages of 18 F-FDG PET/CT in searching for the unsuspected metastasis. [7][8][9][10]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It highlights the unique advantages of 18 F-FDG PET/CT in searching for the unsuspected metastasis. [7][8][9][10]…”
Section: Figurementioning
confidence: 99%
“…Epiglottis and ileum metastases are extremely rare so that we misjudge it as lymphoma or multiple primary cancers at first. It highlights the unique advantages of 18 F-FDG PET/CT in searching for the unsuspected metastasis 7–10 …”
mentioning
confidence: 98%
“…The final pathology supported a diagnosis of metastasis from rectal carcinoma. Rare distant metastasis sites of colorectal cancer include tonsil, 1 kidney, 2 vagina, 3,4 uterus, 5,6 thigh muscle, 7 and thyroid 8 . However, solitary abdominal wall metastasis from rectal adenocarcinoma is very rare.…”
mentioning
confidence: 99%
“…It is reported that FDG PET/CT was helpful in detecting local recurrence, especially extraluminal recurrence of rectal cancer 1–3 . Several cases have reported PET/CT findings of rare metastatic/recurrent pelvic sites from rectal cancer including vagina, 4 uterine, 5,6 and penile, 7 which were hypermetabolic masses with SUVmax ranging from 7.4 to 11. In addition to malignant metastases, active inflammation may also result in high glucose metabolism 8 .…”
mentioning
confidence: 99%